Impact of bowel cancer screening on the management of colorectal cancer. (June 2014) - Hwang, M.‐J.; Evans, T.; Lawrence, G.; Karandikar, S.
Abstract Aim The National Bowel Cancer Screening Programme (NBCSP) was introduced in the West Midlands in 2006. Studies, including the UK Bowel Cancer Screening Pilot, have reported an 18% reduction in mortality. This regional study assesses the impact of screening on elective and emergency colorectal cancer (CRC) surgery. Method Data were extracted from the West Midlands cancer registration database for CRC diagnosed in residents of the West Midlands between 1998 and 2010. Screen‐detected cancers were identified by matching to the NBCSP database. Mode of admission and intervention was obtained by matching to Hospital Episode Statistics and the classification of Interventions and Procedures code. Results Of 42 082 patients diagnosed with CRC, 30 309 received surgical treatment. From 1998 to 2005, the number of patients who underwent emergency surgery increased from 4362 to 18 357, with the proportion each year remaining constant (23.85 ± 0.95% each year). In the screening age group (60–69 years) over the same period, emergency surgery was performed in 918 of 4831 patients (19.15 ± 1.65% each year). Following the introduction of screening, the emergency surgery rate decreased each year, reaching 16% (406/2520) in all patients and 12% (101/829) in the screening age group in 2010 (P < 0.001). These changes in emergency surgery were mirrored by increases in elective surgery. Conclusion The NBCSP has had a positive impact on elective and emergency surgery for CRC in the West Midlands.